2011
DOI: 10.3174/ajnr.a2541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Virchow-Robin Spaces in Alzheimer Disease, Mild Cognitive Impairment, and Normal Aging, Using High-Field MR Imaging

Abstract: BACKGROUND AND PURPOSE:VRSs are the perivascular spaces surrounding the deep perforating arteries in the brain. Although VRS variations with age and disease pathologies have been reported previously, the radiologic characteristics of the VRS in relation to AD are poorly understood. This study investigated the prevalence, spatial distribution, and severity of the VRS in AD, MCI, and older adults who were CN. It also investigated the relationship of the VRS to white matter changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
92
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 27 publications
12
92
1
2
Order By: Relevance
“…12 We found a slight increase in the global score for PVS number with advancing age, which is in accordance with most other studies. 4,8,9,13,[28][29][30][31] Our study sample was relatively healthy, 20 which might partly explain a smaller increase with age than expected, because PVS are presumably correlated with the degree of cerebral small-vessel disease and amyloid deposition with increasing age. 17,18 We did not find a sex difference in the distribution of PVS, even though it has been reported in earlier studies 11,13,16 ; notably, one of these studies comprised a very large population-based sample (n ϭ ϳ1800), in which men were found to have more PVS in the basal ganglia than women, 13 while another large-scale study of patients with ischemic stroke (n ϭ 1090) found that men had more PVS in the white matter than women, but there was no sex difference in the distribution of PVS in the basal ganglia.…”
Section: Discussionmentioning
confidence: 97%
“…12 We found a slight increase in the global score for PVS number with advancing age, which is in accordance with most other studies. 4,8,9,13,[28][29][30][31] Our study sample was relatively healthy, 20 which might partly explain a smaller increase with age than expected, because PVS are presumably correlated with the degree of cerebral small-vessel disease and amyloid deposition with increasing age. 17,18 We did not find a sex difference in the distribution of PVS, even though it has been reported in earlier studies 11,13,16 ; notably, one of these studies comprised a very large population-based sample (n ϭ ϳ1800), in which men were found to have more PVS in the basal ganglia than women, 13 while another large-scale study of patients with ischemic stroke (n ϭ 1090) found that men had more PVS in the white matter than women, but there was no sex difference in the distribution of PVS in the basal ganglia.…”
Section: Discussionmentioning
confidence: 97%
“…First, dilated perivascular spaces are seen in several regions. 7 Perivascular spaces along the ventral aspect of the lentiform nuclei at the level of the anterior commissure are extremely common even in healthy people 35 and thus were not counted. Second, the "large confluent lesions" notion appeared to be broad, because "large" can vary, depending on brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Such common brain changes include global atrophy, white matter injury, smallvessel ischemia, and microhemorrhages. [4][5][6][7][8] These changes are more frequent and more severe in neurodegenerative and neurovascular conditions such as Alzheimer disease (AD), than in healthy aging. [9][10][11] To collectively evaluate multiple common brain changes and their additive effects on brain function, a semi-quantitative rating scale, the Brain Atrophy and Lesion Index (BALI), has been validated.…”
mentioning
confidence: 99%
“…This choice was based on the pronounced presence of dVRSs in these regions, which was reported earlier and is known from our own experience. 4,5 Raters determined dVRS count for each region, with a maximum of 20 per region. Because CSO and BG are visible on multiple slices, the rating was done on a single, predefined slice to decrease inter-and intrarater variability.…”
Section: Rating Protocolmentioning
confidence: 99%
“…Current methods are restricted to studies that only use a single MRI protocol and focus on 1 or 2 brain regions. 3,4,6,8,9,11 A method that can be applied to MRI protocols from different centers and scanners and evaluates the whole brain would strongly facilitate pathogenic and prognostic research on dVRSs. Here, we propose a novel rating method for dVRSs, which we apply in 2 population-based studies, encompassing 3 different scanning protocols.…”
mentioning
confidence: 99%